Analisis Faktor yang Berhubungan dengan Kualitas Hidup pada Orang dengan Skizofrenia (Journal of Telenursing (JOTING), 2024)
This study aims to analyze factors related to quality of life in ODS. The research method uses a quantitative approach with a cross-sectional design. The study results show a significant relationship between family support, self-stigma, self-esteem, work, and physical health with the quality of life of ODS (p-value: 0.000). Family support is The factor most related to the quality of life (0.985). In conclusion, there is a relationship between the quality of life of ODS and family support, self-stigma, self-esteem, physical health, and work, with the dominant factor influencing the quality of life of ODS being the family support factor. Keywords: Quality of Life, Schizophrenia